The end of October - Wright, Lawrence, 1947- (New York : Alfred A. Knopf, 2020)
"At an internment camp in Indonesia, within one week, forty-seven people are pronounced dead with acute hemorrhagic fever. When the microbiologist and epidemiologist Henry Parsons travels there on behalf of the World Health Organization to investigate, what he finds will soon have staggering repercussions across the globe. Matilda Nachinsky, deputy director of U. S. Homeland Security, scrambles to mount a response to what may be an act of biowarfare. Already-fraying global relations begin to snap, one by one, in the face of a pandemic. Henry's wife Jill and their children face diminishing odds of survival in Atlanta and the disease slashes across the United States, dismantling institutions - scientific, religious, governmental - and decimating the population."--Provided by publisher.
This is a Borzoi book.
Keywords: Epidemiologists -- Fiction; Hemorrhagic fever -- Fiction; Physicians -- Fiction; Viruses -- Fiction; Quarantine -- Fiction; Thrillers (Fiction); Action and adventure fiction; Medical fiction